A scenario-based approach for the design of Smart Energy and Water Hub. (15th March 2020) - Roustaei, M.; Niknam, T.; Salari, S.; Chabok, H.; Sheikh, M.; Kavousi-Fard, A.; Aghaei, J.
Abstract: To exploit various energy carriers simultaneously and optimal distribution of energy in smart electrical infrastructure, a smart energy hub (S. E. Hub) concept was emerged. Therefore, the S. E. Hub is an effective solution for creating an efficient energy system. This paper attempts to provide a new management framework for the smart island which consists of Smart Energy and Water Hub (S. E. W. Hub) and microgrid. Also, optimal planning of multiple energy infrastructures of S. E. W. Hub is done considering operational constraints. Furthermore, the impact of the microgrid which includes wind turbines (WTs), photovoltaic power plant (PVPP) and tidal generation on the optimal planning of the S. E. W. Hub is investigated. The planning minimizes the total investment and operation costs as well as the environmental pollutants costs. In the proposed management framework, the balancing of thermal, electrical and water energy is provided. Due to the uncertainties associated with the considered energy sources, an effective scenario-based method is provided to accurately model such uncertainty factors. The validation of the proposed approach is shown through different cases implemented on a real industrial building and the problem is solved in the GAMS environment using CPLEX solver. Highlights: Sea water is desalinated through to produce potable water for human consumption or delivering to the grid. Supplying the water, thermal and electrical energy carriers of a smart island. Providing an optimal planning and sizing scheme for S. E. W. Hub. Investigating the impact of microgrid on planning and sizing for the S. E. W. Hub.